Pengaruh Promosi terhadap Penjualan Polis Asuransi Syariah - Ermayanis Ermayanis; Nurse Fatimah MZ (STAI Auliaurrasyidin Tembilahan, 2020)
This study aimed to determine the effect of promotion on the sales of Islamic insurance policies at PT. Asuransi Takaful Keluarga RO Riau Agency Pekanbaru. This research was motivated by the development of Islamic insurance companies both in terms of assets and in terms of company contributions that have an impact on insurance policy sales. The formulation of the problem in this study was to determine the effect of the relationship promotion on insurance policy sales. This research used quantitative methods with simple linear regression analysis. The sample in this study was 49 respondents. Based on the results of the partial test (t-test), the tcount was 1.391 <t-table 2.016, so the promotion had no significant effect on the variable sales of the insurance policy of PT. Asuransi Takaful Keluarga RO Riau Pekanbaru. The regression results showed that the promotion variable does not affect sales.